2010
DOI: 10.1002/ajmg.a.33707
|View full text |Cite
|
Sign up to set email alerts
|

New intermediate phenotype between MED and DD caused by compound heterozygous mutations in the DTDST gene

Abstract: DTDST mutations cause a spectrum of diastrophic dysplasia disorders characterized by defects of proteoglycans sulfation. Reduction of sulfate/chloride antiporter activity is manifested by lower sulfate uptake and depends on a combination of mutations in DTDST. We analyzed a family with an autosomal recessive form of bone dysplasia. Three affected brothers from this family are compound heterozygotes for C653S/A715V mutations. We classified their phenotype as a new intermediate form between diastrophic dysplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Many patients have “double‐layered” patellae. Clubfoot or metatarsus adductus deformities are also found [Superti‐Furga et al, ; Ballhausen et al, ; Mäkitie et al, ; Czarny‐Ratajczak et al, ]. Our patient's phenotype was in line with previously described patients with rMED although slightly more severe as short limbs were observed already prenatally, and clubfeet and cystic swelling of the external ears were present.…”
Section: To the Editorsupporting
confidence: 87%
See 1 more Smart Citation
“…Many patients have “double‐layered” patellae. Clubfoot or metatarsus adductus deformities are also found [Superti‐Furga et al, ; Ballhausen et al, ; Mäkitie et al, ; Czarny‐Ratajczak et al, ]. Our patient's phenotype was in line with previously described patients with rMED although slightly more severe as short limbs were observed already prenatally, and clubfeet and cystic swelling of the external ears were present.…”
Section: To the Editorsupporting
confidence: 87%
“…Structural mutations which completely abolish the sulfate transporter activity on both alleles of the SLC26A2 cause the severe lethal phenotypes whereas compound heterozygosity of null alleles with missense mutations or other types of mutations preserving residual transporter activity cause milder phenotypes. Intermediate phenotypes sometimes difficult to classify exist between lethal AO2 and severe DTD, or between mild DTD and rMED, and these are usually found in patients with compound heterozygous mutations [Bonafé et al, ; Czarny‐Ratajczak et al, ].…”
Section: To the Editormentioning
confidence: 99%
“…In the mild form of DTD, spinal deformities, such as lordosis, kyphosis, coronal clefts of lumbar vertebrae, and particularly a decrease of the interpedicular distance were frequently observed (26). In the milder form of rMED, platyspondyly was most marked in the lower thoracic and upper lumbar spine (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in SLC26A2 gene result in a continuum clinical spectrum of autosomal recessive chondrodysplasias that include, in increasing order of severity, the lethal achondrogenesis type IB (ACG‐1B; OMIM 600972) and atelosteogenesis type II (AO‐II; OMIM 256050); the diastrophic dysplasia (DTD; OMIM 222600) and the recessive multiple epiphyseal dysplasia (rMED; OMIM 226900). Affected individuals with a more mildly DTD phenotype have been described and they have been classified as DTD variant or as intermediate phenotype between DTD and rMED [Horton et al, ; Czarny‐Ratajczak et al, ; Dwyer et al, ; Barbosa et al, ]. Other cases with phenotypic DTD variant, secondary to mutations in SLC26A2 , overlapping to Desbuquois dysplasia [OMIM 251450], were described and suggested a locus heterogeneity for Desbuquois dysplasia [Miyake et al, ; Panzer et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the phenotypes related to SLC26A2 mutation has been correlated with the residual activity of sulfate transporter resulting of the different types of mutations [Hästbacka et al, ; Karniski, ; Rossi and Superti‐Furga, ]. Literature data have shown that homozygous for null mutation lead to phenotype of ACG‐1B [Karniski, ; Rossi and Superti‐Furga, ]; that compound heterozygous to a null mutation and to a mutation with some residual activity can result in AO‐II, DTD or DTD variant [Hästbacka et al, ; Karniski, ; Rossi and Superti‐Furga, ; Maeda et al, ; Czarny‐Ratajczak et al, ; Dwyer et al, ; Barbosa et al, ], and that homozygous or compound heterozygous mutations with significant residual activity (“mild” mutations) result in rMED [Superti‐Furga et al, ; Karniski, ; Ballhausen et al, ; Mäkitie et al, ; Cho et al, ; Hinrichs et al, ; Barbosa et al, ]. It has also been showed that the “Finnish founder mutation” (c.−26 + 2T>C) acts by severely reduced mRNA levels, but not abolish gene function completely [Hästbacka et al, ] and, that the homozygosis or compound heterozygosity for this mutation can result in variable phenotypes that include AO‐II, DTD, DTD variant or rMED [Hästbacka et al, ; Ballhausen et al, ; Dwyer et al, ].…”
Section: Introductionmentioning
confidence: 99%